Optimization Of Image Processing Techniques In Developing Of Smart Parking System - Bagus Alit Prasetyo; ARI Purno Wahyu Wibowo; Suhendri Suhendri (LPPM STMIK AMIK BANDUNG, 2021)
A parking system is currently a necessity and a common facility found in the campus area of ​​buildings and shops, the management and supervision of this parking lot generally uses third party assistance both in terms of technology and facilities used. At first the parking lot system was still conventional based by using guards in front of the gate and manually recording the entry and exit of the vehicle, a more sophisticated technology was using a camera that was combined with ticketing assistance, officers would check with photos when the car entered and left and strengthened with the use parking tickets, the two technologies have been implemented in many places, the weakness of the system is that there is a need for more than one operator to record and criminal acts will be difficult to detect if a type of vehicle of the same color is stolen because the data from the photos are indistinguishable, To solve this problem, a parking system was created with the help of image processing techniques by recording different types of vehicles even though they were of the same type and color, this system worked using computer vision algorithm rocks with a combination of OCR a Algorithm and surf algorithm, these two algorithms will help record vehicle number-plates while the surf algorithm will record the unique characteristics of the vehicle object in detail so that it will not be change.